ANALYSIS OF THE CAUSES OF PENDING BPJS HEALTH CLAIMS AT THE SPECIAL LUNG HOSPITAL TECHNICAL IMPLEMENTATION UNIT (UPTD) OF THE NORTH SUMATERA - Hasibuan, Rapotan; Hasibuan, Devi Chairani; Karera, Anggi Indah; Ritonga, Fani Rulianda; Syaharani, Latifah; Naution, Rabitha Khailila Ihrom; Sinaga, Mewani (HEARTY, 2026)
The National Health Insurance (JKN) program, administered by BPJS Kesehatan (Social Security Agency for Health), is one of the government’s efforts to ensure access to healthcare services for all. However, its implementation still faces various obstacles, one of which is pending claims. This study aims to analyze the causes of pending BPJS Kesehatan claims at the UPTD (Regional Government Hospital for Lung Disease Control) in North Sumatra Province and identify the dominant factors influencing the delay in claims settlement. This study used a descriptive quantitative method with secondary data obtained from BPJS Kesehatan claims reports and hospital financial data for the period January to July 2025. The data analyzed included the number of claims submitted, eligible claims, pending claims, and the categories of causes for pending claims. The results showed that the total number of claims submitted during this period reached 1,289 files, consisting of 1,224 outpatient claims and 65 inpatient claims. Of these, 77 claims (5.9%) were pending. The main cause of pending claims is the inconsistency of coding in class rates, 92.4% for outpatients and 82% for inpatients due to changes in hospital class rates, while the rest is caused by incomplete files and medical indications. Therefore, the right solution is to implement training activities to improve human resource competency. As a form of intervention, steps that can be taken are to develop Standard Operating Procedures (SOPs) for BPJS Kesehatan claims so that task implementation becomes more focused, uniform, and in accordance with applicable regulations to reduce the number of pending claims and improve hospital financial efficiency.